2023
DOI: 10.3390/cells12141920
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrelation of Molecular Biomarkers and Clinical Phenotype Measures in Fragile X Syndrome

Abstract: This study contributes to a greater understanding of the utility of molecular biomarkers to identify clinical phenotypes of fragile X syndrome (FXS). Correlations of baseline clinical trial data (molecular measures—FMR1 mRNA, CYFIP1 mRNA, MMP9 and FMRP protein expression levels, nonverbal IQ, body mass index and weight, language level, NIH Toolbox, adaptive behavior rating, autism, and other mental health correlates) of 59 participants with FXS ages of 6–32 years are reported. FMR1 mRNA expression levels corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…To better understand the relationship between ICAM5 and MMP-9, Kelly et al (2014) also explored ICAM5 expression in MMP-9 null animals. Recent studies have shown that the synaptic translation of MMP-9 is regulated by FMRP ( Dziembowska and Wlodarczyk, 2012 ; Janusz et al, 2013 ; Gkogkas et al, 2014 ; Lepeta et al, 2017 ; Aishworiya et al, 2023 ). Interestingly, aberrations in dendritic spines that are observed in FXS patients ( Rudelli et al, 1985 ) and Fmr1 KO mice ( Comery et al, 1997 ) have been linked to elevated synaptic levels of MMP-9 ( Dziembowska and Wlodarczyk, 2012 ; Janusz et al, 2013 ; Lepeta et al, 2017 ).…”
Section: Associations Between Synaptic Adhesion Molecules and Fxsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the relationship between ICAM5 and MMP-9, Kelly et al (2014) also explored ICAM5 expression in MMP-9 null animals. Recent studies have shown that the synaptic translation of MMP-9 is regulated by FMRP ( Dziembowska and Wlodarczyk, 2012 ; Janusz et al, 2013 ; Gkogkas et al, 2014 ; Lepeta et al, 2017 ; Aishworiya et al, 2023 ). Interestingly, aberrations in dendritic spines that are observed in FXS patients ( Rudelli et al, 1985 ) and Fmr1 KO mice ( Comery et al, 1997 ) have been linked to elevated synaptic levels of MMP-9 ( Dziembowska and Wlodarczyk, 2012 ; Janusz et al, 2013 ; Lepeta et al, 2017 ).…”
Section: Associations Between Synaptic Adhesion Molecules and Fxsmentioning
confidence: 99%
“…In addition, the CYFIP1 protein acts as a binding partner for FMRP in the regulation of translation initiation ( Busch et al, 2023 ). CYFIP1 interacts with FMRP to form an inhibitory complex that regulates long-term synaptic plasticity ( Aishworiya et al, 2023 ).…”
Section: Associations Between Synaptic Adhesion Molecules and Fxsmentioning
confidence: 99%